Desempenho da tecnologia Bt no controle de espécies de lepidópteros noctuídeos - Campassi, Júlia Carolina (Universidade Federal de São Carlos, 2018)
Among the most important crops for Brazilian agribusiness, soybeans and cotton stand out, both producing millions of tons per harvest. However, various factors limit the full development of these crops, such as the occurrence of pests, which significantly reduce production. Genetically modified plants emerge as a solution for controlling these insects. Therefore, this study aimed to determine the mortality percentage of five species of noctuid lepidopterans when fed with Bt soybeans and cotton, and to evaluate the percentage of leaf damage to soybeans and cotton, with and without Bt technology by the same species. The study was conducted at the Laboratório de Entomologia da Estação Experimental Agrícola BASF, located in Santo Antônio de Posse/SP. Petri dishes lined with moistened filter paper were prepared, containing a cotyledonary leaf or the first pair of true leaves of soybeans or cotton. In each dish, a caterpillar obtained from self-breeding was added. A total of 25 treatments (10 for soybeans and 15 for cotton) with 6 repetitions each were evaluated. Assessments were made on the first and seventh days after setup, recording caterpillar mortality and the damage caused by them. The results were subjected to analysis of variance and Tukey's test with a 5% significance level. The Bt technology Intacta RR2 PRO (Cry1Ac) in soybeans significantly reduced the percentage of damage caused by the species Chrysodeixis includens and Helicoverpa armigera, with no effect on the Spodoptera spp. complex. Regarding survival, the only affected species were C. includens and H. armigera, which had low survival rates. For cotton, the Bollgard II (Cry1Ac+Cry2Ab2) and Widestrike (Cry1F+Cry1Ac) technologies reduced the percentage of damage and survival of Chrysodeixis includens, Helicoverpa armigera, Spodoptera eridania, and Spodoptera cosmioides, with no effect on Spodoptera frugiperda. In conclusion, the Intacta Bt technology affects Chrysodeixis includens and Helicoverpa armigera, while Bt technologies for cotton affect Chrysodeixis includens, Helicoverpa armigera, Spodoptera eridania, and Spodoptera cosmioides.
Performance of Bt technology in the control of species of noctuid lepidopterans
Keywords: Bacillus thuringiensis; Glycine max; Gossypium hirsutum; Spodoptera spp.; Lagartas desfolhadoras; Defoliating caterpillars; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE